An Analysis of the Philippine Business Process Outsourcing Industry - Nedelyn Magtibay-Ramos; Gemma Estrada; Jesus Felipe (Asian Development Bank (ADB), 2007)
"Nedelyn Magtibay-Ramos, Gemma Estrada, and Jesus Felipe provide an analysis of the business process outsourcing (BPO) industry in the Philippines. The paper provides a profile of the BPO sector; makes comparisons with other large BPO providers; and uses input–output tables to estimate intersectoral linkages and the potential impact of the sector on employment. Constraints on the sector's growth are discussed."
hdl:11540/1849
Keywords: 330; Auslandsverlagerung; Outsourcing; Welt; Philippinen; Wirkungsanalyse; Entwicklung; Philippinen